Nearby Functional results for the treatment of rupture of medial meniscus cartilage in arthroscopy, Comparison between traditional method and method with the help of laser. - ALI, Nazem (Latakia University Journal -Medical Sciences Series, 2018)
The study presents a comparison between two methods of treatment of the Rupture of the medial meniscus cartilage in traditional arthroscopic method and laser assisted method. The study included 20 cases, 10 of which were treated in one way. The nearby functional results were evaluated after surgery, The researcher reached the following results : Laser treatment for cases of rupture of cartilage is better in surgical time ,The duration of hospital stay, postoperative pain relief, reduced knee hemarthrosis , and Improved walking ability, as well as a marked decrease in the time of the discontinuity of the work. النتائج الوظيفية القريبة لعلاج تمزق الغضروف الهلالي الأنسي بالتنظير المفصلي مقارنة بين الطريقة التقليدية والطريقة بمساعدة الليزر المفصلي يقدم البحث مقارنة بين طريقتين لعلاج تمزق الغضروف الهلالي بطريقة التنظير المفصلي التقليدي والطريقة بمساعدة الليزر ,حيث شملت الدراسة 20 حالة كل عشرة منها عولجت بطريقة واحدة وتم تقييم النتائج القريبة بعد الجراحة وتوصل الباحث لنتائج أهمها: قدم العلاج بالليزر المفصلي لحالات تمزق الغضروف الهلالي أفضلية من ناحية وفرة زمن العمل الجراحي و فترة الإقامة بالمشفى , تخفيف حدة الألم التالي للجراحة و تقليل الانصباب المفصلي في الركبة, وتحسين إمكانية الاستناد على الطرف(السير) كما لوحظ انخفاض واضح في زمن الانقطاع عن العمل.